KEGAGALAN HAK MILIK DAN KONFLIK TENURIAL DI KAWASAN HUTAN RIAU: EVALUASI TORA - Siti Fadilla; Taryono Taryono (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study examines the structural causes of property rights failure in Riau’s forest areas, evaluates the effectiveness of Agrarian Reform through TORA (Land Object of Agrarian Reform) and Social Forestry policies, and identifies measures to strengthen agrarian justice and tenure security. Using a qualitative approach, the study analyzes secondary data from scientific publications, government reports, policy documents, conflict records, and official statistics. The conflict between the Batin Baringin Sakai Indigenous Community and PT Arara Abadi serves as a representative case study. Property Rights Theory and Institutional Economics are employed as the main analytical frameworks. The findings indicate that property rights failure is primarily caused by incompatibility between customary and formal legal systems, overlapping land and forestry regulations, and top-down forest area designation policies. TORA has made substantial progress in asset legalization, achieving 87.69% of its target by 2023, but forest-area land redistribution remains limited, reaching only 9.26% of the national target. Social Forestry expanded to 7.08 million hectares by May 2024, although implementation continues to face administrative, institutional, and economic challenges.This study contributes to the literature by integrating Property Rights Theory and Institutional Economics to explain persistent tenurial conflicts and by comparing TORA and Social Forestry as complementary agrarian reform instruments. Policy recommendations include accelerating recognition of indigenous territories, improving inter-agency coordination, strengthening land redistribution, simplifying Social Forestry procedures, and enhancing community economic empowerment.